Ali je Slovenija res pomorska država - Pavliha, Marko (Podjetje in delo, 2024)
The author answers the question in the title with an affirmative response, stating that Slovenia has always been a coastal and maritime country. Such a position is supported by geography, the national coat of arms, Slovenian maritime tradition and maritime identity, the tradition of maritime education, maritime law, economics and ecology, and Euro-Slovenian maritime affairs. At the same time, he notes that Slovenia is insufficiently maritime oriented, as it has wasted too many brilliant achievements and opportunities, but that we can learn a lot from mistakes and ensure a better maritime future.